Lingvo-cognitive semantics of phraseological units used with somatism “hand” in Japanese - Tazabekova, G.B. (Journal of Oriental Studies, 2021)
This article is devoted to the somatic phraseology of the Japanese language. This term refers to phraseology that contain the names of parts of the human body. The article defines the linguocognitive semantics of Japanese phraseology, used with somatism “hand”. The purpose of the study is to reveal the semantic structure of phraseology in terms of cognitive linguistics. For this, first of all, on the basis of lexicographic sources, an analysis of the definitions of the word “hand” was carried out and its semes were determined. At the next stage connotative components of the meaning of phraseology was revealed and frame-analysis was carried out. On the basis of these frames relating to various aspects of human life, was developed frame classification of somatic units used with the lexeme “hand”. By the analysis of this frame classification through the prism of the national worldview of the ethnos, conclusions about the specific ethno-cognitive features of the Japanese people, reflected in the phraseology of each frame group were generalized, and the results of the research were presented. A comprehensive study of the meaning and motives of the Japanese phraseology is of great importance for a deeper understanding the knowledge of Japanese people about true reality, the system of principles, views and beliefs that determine the attitude f society as a whole to the world around them. Key words: Japanese language, somatism, phraseology, semantics, frame.